Atrial fibrillation is associated with an increased risk of ventricular arrhythmias and sudden death in the general population. (19th May 2022) - Fawzy, AM; Bisson, A; Bodin, A; Herbert, J; Lip, GYH; Fauchier, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) has been linked to an increase in the risk of ventricular arrhythmias. Purpose: We aimed to investigate whether AF is associated with an increased risk of ventricular tachycardia (VT), ventricular fibrillation (VF) and sudden death (SD). Methods: Hospitalised patients from 2013 with and without AF were identified from the French National database and included if they had at least 5 years of follow-up. Results: Over a median follow-up period of 5.4 years (interquartile range (IQR) 5.0-5.8 years), a total of 3345638 patients were identified. Of these, 312226 had AF and 3033412 did not have AF. After multivariable analysis, the predictors significantly associated with VT, VF and SD included age, sex, hypertension, diabetes mellitus, heart failure, history of pulmonary oedema, valve disease, dilated cardiomyopathy, coronary artery disease, vascular disease, AF, smoking, dyslipidaemia, obesity, alcohol related diagnoses, chronic kidney disease, lung disease, liver disease, inflammatory diseases, anaemia, previous cancer, poor nutrition, cognitive impairment, and frailty. The incidence of VT, VF and SD was higher in those with AF compared to those without AF (2.23%/year vs. 0.56%/year). AF was associated with a higher risk of incident outcomes compared to no AF, hazard ratio (HR) 3.657 (confidence interval (CI) 3.604-3.711). After adjustments were made for confounders (Figure 1), this increased risk was still significant HR 1.167 (CI 1.111-1.226). A 1:1 propensity score matched analysis was also performed (n=289, 332 in each group), demonstrating the significantly increased risk of ventricular arrhythmias and SD in patients with AF compared to those without AF, HR 1.339 (CI 1.313-1.366). Conclusion: The findings from our study AF indicate that AF is associated with an increased risk of VT, VF and sudden death in the general population.